(untitled) (Ustozlar uchun, 2024)
The paper focuses on the task of further development of youth as a comprehensively intellectually developed personality, creators of the future of our country, support and widespread involvement in science of gifted youth engaged in scientific activities, as well as the creation and enhancement of the scientific potential of reputable scientific schools. The article examines the invaluable importance of the immortal scientific works of al-Beruni in the development of world scientific thought and in the education of intellectual youth.